Cascading effects of predator activity on tick-borne disease risk - Hofmeester, Tim R; Jansen, Patrick A; Wijnen, Hendrikus J; Coipan, Elena C; Fonville, Manoj; Prins, Herbert H T; Sprong, Hein; van Wieren, Sipke E (Proceedings of the Royal Society B : Biological Sciences, 2017)
Predators and competitors of vertebrates can in theory reduce the density of infected nymphs (DIN)-an often-used measure of tick-borne disease risk-by lowering the density of reservoir-competent hosts and/or the tick burden on reservoir-competent hosts. We investigated this possible indirect effect of predators by comparing data from 20 forest plots across the Netherlands that varied in predator abundance. In each plot, we measured the density of questing nymphs (DON), DIN for three pathogens, rodent density, the tick burden on rodents and the activity of mammalian predators. We analysed whether rodent density and tick burden on rodents were correlated with predator activity, and how rodent density and tick burden predicted DON and DIN for the three pathogens. We found that larval burden on two rodent species decreased with activity of two predator species, while DON and DIN for all three pathogens increased with larval burden on rodents, as predicted. Path analyses supported an indirect negative correlation of activity of both predator species with DON and DIN. Our results suggest that predators can indeed lower the number of ticks feeding on reservoir-competent hosts, which implies that changes in predator abundance may have cascading effects on tick-borne disease risk.